HOMELESSNESS IRONICALLY ACCEPTED BY HRABAL VERSUS KUNDERA’S SUPPRESSED HOMESICKNESS - Češka, Jakub (Porównania, 2012)
By means of using the topic of sentiment, the contrast between the writing of Milan Kundera and Bohumil Hrabal is shown. All the typically acknowledged characteristics are reversed. Although Kundera is assigned a label of a cynical, unromantic and antisentimental author and Hrabal is often classified as an author of sensitive understanding, it is through the topic of the home that the reversed can be shown. The arguments can be found on the level of écriture: Kundera’s writing is distinctive, semantically detailed and possesses internal focalisation. These characteristics allow him to enter the topic of condemnation, renegation and the polarisation of the alternative between the home and the foreign. Each of the authors proposes a different answer to the question on homelessness: Hrabal uses the figure of cynically accepted homelessness whereas Kundera a suppressed sentiment which emanates with homelessness.